A comparative study and optimization of enhanced integrated geothermal flash and Kalina cycles: A thermoeconomic assessment. (1st November 2018) - Mokarram, N. Hassani; Mosaffa, A.H.
Abstract: This work deals with a comparative study for different basic and enhanced integrated geothermal flash and Kalina cycles from the thermoeconomic point of view. The considered cycles include different combination of basic and modified Kalina cycles, basic geothermal single flash cycle, double flash cycle and its enhanced modes. The basic Kalina cycle is modified by employing a two-phase expander instead of the throttling valve. Also, in order to enhance geothermal flash cycle, the geofluid steam is heated by a part of the heat contained in the geofluid at the wellhead before entering the turbine. Moreover, the effects of different key parameters on the thermodynamic and economic performances are investigated and optimized using the genetic algorithm method. The results show that when enhanced double flash/modified Kalina cycle is used, generated power increases by 6% compare to the basic cycle under the optimum operating condition. In this case, the increment of unit production cost is ignorable compared to the basic cycle. The exergy destruction rate of each component is calculated under the optimum operating condition. For all considered cycles, the highest value of exergy destruction rate belongs to the evaporator. Highlights: Enhanced geothermal flash cycle integrated with modified Kalina cycle is proposed. Thermoeconomic performance of proposed cycle is compared with similar basic cycle. Basic and enhanced proposed cycles are optimized using genetic algorithm. An improvement of 6% is achieved in generated power by using enhanced cycles. Enhancing the basic cycle leads to the ignorable increase in unit production cost.